FAKTOR SOSIAL DAN PENYEBAB STEREOTIP PEREMPUAN DALAM BAHASA INDONESIA DALAM RANAH RUMAH TANGGA - Suyanto Suyanto (KAJIAN SASTRA, 2010)
Women stereotype reflected in Indonesian language shows male superiority power upon female in society that belong to patriarchy ideology. In this kind of society female is always in a position of subordination which are determined by among others, history, culture, and social factors. Social factors that influence the stereotype of female in Indonesian are sex, education, and employment. In this case, education significantly leaves the other two behind. The more education reason are the more aware of gender sensitive. Others factors which also have strong influence upon women stereotype in Indonesian language are culture, and more specific is religionKey words: women stereotype, social factors, Indonesian language, household http://ejournal.undip.ac.id/index.php/kajiansastra/editor/submission/2675